Angelologia w pismach Justyna, Tacjana i Atenagorasa z Aten - Misiarczyk, Leszek (Vox Patrum, 2023)
The aim of the study was to analyze the texts of Justin, Tatian and Athenagoras on the subject of angels. I do this on three points: the creation of angels by God/Logos as free beings (1); the tasks of angels (2) the sin of angels and the final annihilation of demons/evil angels. All three authors emphasize that God created angels and people as free beings, and therefore also responsible for their actions, and entrusted them with the care of people and his creation. However, some angels were deceived by the first angel (Tatian) or by the hostile power (Athenagoras), who let himself be carried away by vain glory, broke all ties of dependence on God and wanted to appropriate the deity. He turned into a demon and his followers into a host of demons. Athenagoras combines the concept of Tatian and Justin, stating that the power/spirit to whom God entrusted the management of matter and its forms, insulted its own essence and the power entrusted to it, and the angels from the first vault sinned by intercourse with women, which gave birth to giants. Tatian’s and Athenagoras’ concept of the sin of angels is definitely less mythical than that of Justin. According to Tatian and Athenagoras, this state of fallen angels is irreversible.